Design and implementation of a direct torque control of induction machine utilizing a digital signal processor and the field programmable gate arrays - Toh, C. L. (IEEE, 2006)
Employing both DSP and FPGA in motion control will This is because the lack of flexibility to modify or to adapt the give advantages of rapid prototyping and higher switching design to different types of motor drives, once the chip is built frequency in Direct Torque Control (DTC) drive. This paper [1], [5]. A special class of ASIC known as Field Programmable presents a high performance DTC induction motor drive with Gate Arrays (FPGA's) offers a realistic alternative. It can constant switching frequency and low torque and flux ripples. significantly reduce design risk since a design error can be The experimental results prove the feasibility of the proposed corrected immediately and intensively by re-programming the controllers, which is achieved using the combination of a DSP FPGA and an FPGA.